The Bestseller List and its (Dis)contents - Rasmus Grøn (Akademisk Kvarter, 2013)
‘Bestseller’ is a pivotal and highly influential concept in the current literary market, where a title’s presence on a bestseller list also serves to reinforce the title’s bestseller status. In spite hereof, there is a lack of exact knowledge of bestselling patterns on the Danish book market, as well as a conceptual vagueness regarding the distinction between ‘the best and the rest’: how to define a bestseller and differentiate it from the remaining titles on the market? These two issues are addressed in the following article. Firstly, a Top 40 list of the bestselling fiction books from Danish book stores in the period of 2008-11 is presented, and its contents are analysed in terms of genre, nationality, and thematic qualities. Hereafter, the bestselling list serves as a point of departure for a discussion of the divergent and contingent criteria underlying possible definitions of bestsellers and their inclusion on bestseller lists, thereby developing a more facetted picture of the bestseller concept. Lastly, Robert Escarpit’s temporal distinction between fastsellers, steadysellers and bestsellers is related to the article’s empirical data in order to discuss a widespread assumption of the volatility of the bestseller.